2017
DOI: 10.1016/j.omtn.2017.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Broad-Spectrum Inhibition of Respiratory Virus Infection by MicroRNA Mimics Targeting p38 MAPK Signaling

Abstract: The majority of antiviral therapeutics target conserved viral proteins, however, this approach confers selective pressure on the virus and increases the probability of antiviral drug resistance. An alternative therapeutic strategy is to target the host-encoded factors that are required for virus infection, thus minimizing the opportunity for viral mutations that escape drug activity. MicroRNAs (miRNAs) are small noncoding RNAs that play diverse roles in normal and disease biology, and they generally operate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 66 publications
(89 reference statements)
1
50
0
Order By: Relevance
“…Recently, deficiency of neuronal p38alpha MAPK has been shown to attenuate amyloid pathology in AD mouse and cellular models [75]. Interestingly, mir-744, mir-124a and mir-24 mimics have been shown to suppress both p38 MAPK expression and activation [76]. Similarly, LPS treatment of the hippocampal HT-22 cells has been shown to downregulate mir-132 expression which in turn upregulates the expression of the target gene TRAF6 causing activation of the NFκB and MEK/ERK pathways [77].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, deficiency of neuronal p38alpha MAPK has been shown to attenuate amyloid pathology in AD mouse and cellular models [75]. Interestingly, mir-744, mir-124a and mir-24 mimics have been shown to suppress both p38 MAPK expression and activation [76]. Similarly, LPS treatment of the hippocampal HT-22 cells has been shown to downregulate mir-132 expression which in turn upregulates the expression of the target gene TRAF6 causing activation of the NFκB and MEK/ERK pathways [77].…”
Section: Discussionmentioning
confidence: 99%
“…In this case, the mechanism seems to be similar to the one described in the case of miR-21 and CVB3, with decreased levels of phosphorylated p38 showing a reduced activation of this component. Furthermore, a significant reduction in the expression of p38 MAPK has also been demonstrated through decreased levels of proteins (McCaskill et al, 2017).…”
Section: Mapk Signaling Pathwaymentioning
confidence: 98%
“…In this case, the miRNAs involved are miR-24, miR-124, and miR-744. However, besides the decrease in the activation of p38 component due to a lack of phosphorylation, there has also been demonstrated a reduction in the overall levels of the same member (McCaskill et al, 2017;He et al, 2019).…”
Section: Figure 3 | (A)mentioning
confidence: 99%
“…By using chemical inhibitors as well as knockout cell lines, it was shown that MAPK p38-dependent phosphorylation of TRIM28 facilitates a functional switch leading to increased cytokine levels in cells infected with highly pathogenic viruses (Krischuns et al 2018). Besides its role in the induction of pro-inflammatory and antiviral cytokines, there have been reports of a virus-supportive function of MAPK p38 observed after inhibition of the pathway with different p38 inhibitors (Marchant et al 2010;Choi et al 2016;McCaskill et al 2017). Deeper investigation provided evidence of a potential role of p38 in Toll-like receptor 4-mediated virus internalization, which is based on p38catalyzed phosphorylation of early endosome antigen 1 (EEA1), which increases endocytotic activity.…”
Section: Stress-induced Mapks Jnk and P38mentioning
confidence: 99%